Sebuah PEMUPUKAN N-P-K DAN POC TERHADAP PERTUMBUHAN, FISIOLOGI DAN HASIL TANAMAN JEWAWUT (Setaria Italica) - Ahadiyat Yugi Rahayu; Wildan Zaki Mubarok; Tamad Tamad (Jurnal Penelitian Pertanian Terapan, 2023)
Jewawut (Setaria italica) is a cereal plant that has characteristics like rice. The use of millet as food has not been optimal for production. Millet production can be influenced by several factors, including soil conditions, plant varieties, climate and cultivation techniques. The aim of this research is to reduce the use of inorganic N-P-K fertilizers and obtain the optimal N-P-K fertilization dosage with a combination of Liquid Organic Fertilizer (LOF) treatment. The research was done on dry land in Purwanegara Village, North Purwokerto District and in the Laboratory at the Faculty of Agriculture Jenderal Soedirman University, begin at May 2019 until October 2019. The research design was a randomized block design (RBD). There are two factors was be examined, the dose of N-P-K fertilizer and the concentration of two types of POC. The recommended dosage of N-P-K fertilizer for millet is N 138 kg / ha, P2O5 54 kg/ha, and K2O 45 kg/ha. The N-P-K fertilization treatment was divided into 25%, 50%, 75% 100%. Combined with LOF consisting of control, bamboo root  LOF concentrations of 5 ml/l and 10 ml/l, Rabbit urine LOF 50% with concentrations of 2 ml / l and 4ml / l. The results showed that the growth characters due to application of 50% N-P-K fertilization equal with 100% N-P-K on plant height. Application of 50% N-P-K gained the optimum of flowering age and yield per hectare. Liquid organic fertilizer had not improved on growth and yield of foxtail millet yet.